Ảnh hưởng của mật độ dòng, nồng độ chì nitrat và nhiệt độ của dung dịch điện ly đến hình thái, cấu trúc của lớp PbO2 kết tủa điện hóa trên vật liệu nền thép - Lan, Ngô Thị; Tú, Doãn Anh; Loan, Tô Thanh; Mai Thanh, Đinh Thị (Vietnam Journal of Chemistry, 2016)
In this work, results of morphology, phase composition of PbO2 layers on mild steel covered by Fe3O4 film formed by electrochemical method in NaOH media (PbO2/Fe3O4ĐH/steel) were showned. Different parameters such as current density, concentration of lead nitrat, temperature of electrolyte, at pH = 4 were optimized. In the range of concentration from 0.25 mol/L to 1 mol/L of Pb(NO3)2, two phases of a-PbO2 and b-PbO2 were formed with the compact tetragonal shapes and different dimensions. However, b-PbO2 form dominated, the percent of b-PbO2 form increases when concentration of Pb(NO3)2 in elctrolyte rises. Phase composition of PbO2 layers  were affected strongly by temperature of electrolyte, at 15 oC, b-PbO2 form reached 81.87 % and a-PbO2 only 14.92 %. However, at 50 oC, a-PbO2 form dominated with 91.93 %, and b-PbO2 only 4.33 %. Keywords. Electrodeposition, b-PbO2, a-PbO2 , mild steel.